Cucurbituril-based supramolecular engineered nanostructured materials. Issue 2 (19th November 2014) - Gürbüz, Sinem; Idris, Muazzam; Tuncel, Dönüs
Abstract : Nanostructured materials, including nanoparticles, nanocomposites, vesicles, and rods, have been prepared by taking advantage of the interesting features of cucurbituril homologues. Abstract : Cucurbituril (CB) is a unique macrocycle with a rigid symmetrical structure, which is composed of two identical hydrophilic portals decorated with partially negatively charged carbonyl groups and a hydrophobic cavity. A number of different nanostructured materials, including nanoparticles, nanocomposites, vesicles and rods, have been prepared by taking advantage of the varying cavity size of the CB homologues, their ability to accommodate more than one guest in their cavities, their rigid symmetrical structures, as well as the water solubility of CB7. These nanostructures could find a wide range of potential applications in the areas of self-healing materials, nanomedicine, plasmonics, and nanocatalysis. Here, we review the recent progresses in the synthesis, properties and application of CB-based supramolecular engineered nanostructures, which are either constructed through CB-assisted self-assembly or from post-functionalized-CB homologues.